The Impact Of Financial Ratios On Stock Returns: A Study Of Companies In The Sri-kehati Index 2014-2022 - Hasanudin, Hasanudin (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to identify how much influence Return On Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), and Earning Per Share (EPS) have on Stock Returns. The population focused on in this study are companies listed in the SRI-Kehati Index during the period 2014-2022, with a span of the last 9 years. The sample selection method used is purposive sampling, where 10 companies were carefully selected as research samples. Data analysis was carried out using panel data regression with a significance level of 0.05, and utilizing STATA software to support the analysis process. The results showed that the variables Return On Asset (ROA) and Earning Per Share (EPS) have a positive and significant influence on Stock Returns. This shows that the rate of return on assets (ROA) and earnings per share (EPS) contribute substantially to a company's stock performance. The higher the ROA and EPS, the more likely it is that stock returns will also increase. The results of the study also show that the Current Ratio (CR) and Debt to Equity Ratio (DER) variables do not have a significant effect on Stock Returns. This raises questions about the relevance of the two ratios in predicting stock performance. This finding may be a consideration for investors and decision makers in analyzing the factors that affect a company's stock performance.